Genome-wide identification of the auxin response factor (ARF) gene family in Magnolia sieboldii and functional analysis of MsARF5 - Mei, Mei; Ai, Wanfeng; Liu, Lin; Xu, Xin; Lu, Xiujun (Frontiers in Plant Science, 2022)
Auxin plays an essential role in flowering, embryonic development, seed dormancy, and germination. Auxin response factors (ARFs) are plant-specific key transcriptional factors in mediating the gene expression network of auxin signaling. Although ARFs in model plants such as Arabidopsis had been well characterized, their identities and potential roles in non-model plants are less studied. Here, we performed genome-wide identification of ARFs in Magnolia sieboldii K. Koch, a primitive species with high taxonomic importance and medicinal values. We found 25 ARF genes in M. sieboldii, which were widely distributed across multiple chromosomes. Based on sequence similarity, the encoded proteins could be either transcriptional repressors or activators. Gene expression analysis showed a dynamic pattern for many ARFs including MsARF5 during seed germination. In addition, overexpressing of MsARF5 showed that it restores many developmental defects in the Arabidopsis mutant. Moreover, two phenotypically distinct transgenic Arabidopsis lines were obtained, indicating a link between gene expression levels and developmental phenotypes. Taken together, we provided a systematic investigation of the ARF gene family in M. sieboldii and revealed an important role of MsARF5 in mediating auxin signaling.